2020
DOI: 10.3390/pathogens9070578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Infectious Spleen and Kidney Necrosis Virus (ISKNV), Nervous Necrosis Virus (NNV) and Ectoparasites in Juvenile Epinephelus spp. Farmed in Aceh, Indonesia

Abstract: A cross-sectional survey was used to estimate the prevalence of infections with the Infectious spleen and kidney necrosis virus (ISKNV, Megalocytivirus), nervous necrosis virus (NNV, Betanodavirus), and infestations with ectoparasites during the rainy season in juvenile grouper (Epinephelus spp.) farmed in Aceh, Indonesia. The survey was intended to detect aquatic pathogens present at 10% prevalence with 95% confidence, assuming 100% sensitivity and specificity using a sample size of 30 for each diagnostic tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…ISKNV was also identi ed from various marine sh species in other Southeast Asian countries including Indonesia, Vietnam, Malaysia, and Singapore [11,23,39,46]. Most of the ISKNV found in these countries were genotype I, similar to our study, which indicated the widespread of this ISKNV genotype in Southeast Asia.…”
Section: Discussionsupporting
confidence: 83%
“…ISKNV was also identi ed from various marine sh species in other Southeast Asian countries including Indonesia, Vietnam, Malaysia, and Singapore [11,23,39,46]. Most of the ISKNV found in these countries were genotype I, similar to our study, which indicated the widespread of this ISKNV genotype in Southeast Asia.…”
Section: Discussionsupporting
confidence: 83%
“…The scale bar represents the nucleotide substitution per site associated with mortality in farmed barramundi (Dong et al, 2017), bluegill sunfish (Liu et al, 2019), Epinepheleus spp. (Sah Putra et al, 2020), mandarin fish (He et al, 2000), Murray cod (Go et al, 2006), pearl giant grouper (Huang et al, 2020) and ornamental fish species (Jung-Schroers et al, 2016;Tanaka et al, 2014 ). Therefore, ISKNV is considered as an emerging pathogen in both marine and freshwater aquaculture in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…In another study in the same region, two-step PCR showed the percentage of ISKNV-like viruses detected in different seasons (22.1% winter, 27.8% summer, 34.0% autumn, and 17.0% spring) and proved that water temperature is a key condition for ISKNV outbreaks [ 16 ]. In other regions, such as Malaysia and Indonesia, Megalocytivirus have been observed in water temperatures ranging from 28°C to 32°C annually [ 85 ], with the highest mortality occurring at 27°C [ 87 ].…”
Section: Risk Factorsmentioning
confidence: 99%